Powierzchniowe Ogrzewanie Półprzestrzeni Warstwowej - Vodička, V. (Engineering Transactions, 1963)
The object of the paper is to determine the non-steady temperature field in the body x ≥ 0, - ∞ < y < ∞, - ∞ < z < 0 composed of n homogeneous isotropic layers xk-1 < x < xm, 1 < k < n-1, x0 = 0, x ≥ xn-1, -∞ <y, z < ∞. Stating at the moment f = 0 the body is heated on the surface x = 0, the heat being supplied at the rate q (y, z). The initial temperature is zero. The general results are applied to the case of homogenous semi-space. A certain Oosterkamp’s problem is solved as a simple special case.